Cognitive illness representations among Israeli Arabs diagnosed with depression and their relationship with health-related quality of life. (May 2022) - Abo-Rass, Fareeda; Werner, Perla; Shinan-Altman, Shiri
Background: The number of studies that have assessed cognitive illness representations among people diagnosed with depression, and their relationship to health outcomes, has clearly grown. Nevertheless, the relationship between cognitive illness representations and health-related quality of life (HRQoL) has received very little research attention. Aims: This study examined cognitive illness representations, based on the self-regulation model (SRM), and the contribution of each dimension of these cognitive illness representations to health-related quality of life (HRQoL) among Israeli Arabs diagnosed with depression. Methods: A convenience sample of 160 Israeli Arabs with depression completed measures of cognitive illness representations (identity, timeline, consequences, personal control, treatment control, and coherence), HRQoL, and sociodemographic and health characteristics. Results: Participants reported high levels of negative perceptions in the identity, timeline, and consequences dimensions, and moderate levels in the dimensions of personal control, treatment control, and coherence. Also, participants reported low levels of HRQoL. Identity, consequences, and coherence were found to be the main determinants of HRQoL. Conclusion: This study underlines the crucial role of the identity, consequences, and coherence dimensions in the HRQoL of individuals diagnosed with depression. The findings indicate that clinical interventions targeting cognitive illness representations of individuals with depression, and in particular identity, consequences, and coherence, might be helpful in improving the HRQoL of this population.